A Multifaceted Role of Tryptophan Metabolism and Indoleamine 2,3-Dioxygenase Activity in Aspergillus fumigatus–Host Interactions - Choera, Tsokyi; Zelante, Teresa; Romani, Luigina; Keller, Nancy P. (Frontiers in Immunology, 2018)
Aspergillus fumigatus is the most prevalent filamentous fungal pathogen of humans, causing either severe allergic bronchopulmonary aspergillosis or often fatal invasive pulmonary aspergillosis (IPA) in individuals with hyper- or hypo-immune deficiencies, respectively. Disease is primarily initiated upon the inhalation of the ubiquitous airborne conidia—the initial inoculum produced by A. fumigatus—which are complete developmental units with an ability to exploit diverse environments, ranging from agricultural composts to animal lungs. Upon infection, conidia initially rely on their own metabolic processes for survival in the host’s lungs, a nutritionally limiting environment. One such nutritional limitation is the availability of aromatic amino acids (AAAs) as animals lack the enzymes to synthesize tryptophan (Trp) and phenylalanine and only produce tyrosine from dietary phenylalanine. However, A. fumigatus produces all three AAAs through the shikimate–chorismate pathway, where they play a critical role in fungal growth and development and in yielding many downstream metabolites. The downstream metabolites of Trp in A. fumigatus include the immunomodulatory kynurenine derived from indoleamine 2,3-dioxygenase (IDO) and toxins such as fumiquinazolines, gliotoxin, and fumitremorgins. Host IDO activity and/or host/microbe-derived kynurenines are increasingly correlated with many Aspergillus diseases including IPA and infections of chronic granulomatous disease patients. In this review, we will describe the potential metabolic cross talk between the host and the pathogen, specifically focusing on Trp metabolism, the implications for therapeutics, and the recent studies on the coevolution of host and microbe IDO activation in regulating inflammation, while controlling infection.